2021
DOI: 10.1364/oe.413035
|View full text |Cite
|
Sign up to set email alerts
|

Development of a laser heterodyne spectroradiometer for high-resolution measurements of CO2, CH4, H2O and O2 in the atmospheric column

Abstract: We have developed a portable near-infrared laser heterodyne radiometer (LHR) for quasi-simultaneous measurements of atmospheric carbon dioxide (CO2), methane (CH4), water vapor (H2O) and oxygen (O2) column absorption by using three distributed-feedback diode lasers as the local oscillators of the heterodyne detection. The developed system shows good performance in terms of its high spectral resolution of 0.066 cm−1 and a low solar power detection noise which was about 2 times the theoretical quantum limit. Its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…In 2014, Rodin A et al used a 1.65 μm optical fiber LHR to achieve absorption measurements of CH 4 and CO 2 with a signal-to-noise ratio (SNR) of 120 with an exposure time of 10 min [15]. The groups of Gao X and Kan R also reported the study of optical fiber LHR [16,17]. However, the above studies generally focus on the measurement of carbon-containing GHGs, and there are few studies on the content and characteristics of water vapor concentration.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Rodin A et al used a 1.65 μm optical fiber LHR to achieve absorption measurements of CH 4 and CO 2 with a signal-to-noise ratio (SNR) of 120 with an exposure time of 10 min [15]. The groups of Gao X and Kan R also reported the study of optical fiber LHR [16,17]. However, the above studies generally focus on the measurement of carbon-containing GHGs, and there are few studies on the content and characteristics of water vapor concentration.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Compared with current FTS, LHR offers merits: high sensitivity, high spectral/spatial resolution, and cost-effective compact instrument size. [2][3][4][5][6][7][8] In the near-infrared (IR), LHR has developed rapidly in recent years. 9 Wilson et al, [10][11][12] Rodin et al, 13,14 and Wang et al 15 developed LHRs applying distributed feedback (DFB) lasers as local oscillators (LOs) for measuring CO 2 and CH 4 in the atmospheric column.…”
Section: Introductionmentioning
confidence: 99%
“…Ground‐based passive laser heterodyne radiometer (LHR), similar to the Fourier‐transform spectrometer (FTS), 1 uses the Sun as a signal source to carry out long‐term, long‐distance, and remote sensing of atmospheric gases 2,3 . Compared with current FTS, LHR offers merits: high sensitivity, high spectral/spatial resolution, and cost‐effective compact instrument size 2–8 …”
Section: Introductionmentioning
confidence: 99%
“…One of the most commonly used methods for the retrieval of mixing ratios from LHR data is the optimal estimation method (OEM) developed by C. D. Rodgers, to which vertical profiles can be fed from sources such as European Centre for Medium-Range Weather Forecasts (ECMWF) or National Centers for Environmental Prediction (NCEP) [3][4][5][6]. Weidmann et al demonstrated the application of this method to LHR data using pressure, temperature, and volume mixing ratios extracted from ECMWF [7].…”
Section: Introductionmentioning
confidence: 99%